A Critical Survey of Biomineralization Control, Mechanisms, Functions and Material Properties - Engel, Jürgen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This monograph provides a comprehensive and up-to-date approach on biomineralization. The topical focus of the book lies on the question of how matrix proteins and cells catalyze and regulate mineralization in organisms. Recent advances in the understanding of biomineralization help to better understand biomaterials, in particular their mechanical properties. The target audience primarily comprises practitioners and research experts in the field, but the book may also be beneficial for graduate students.
Introduction -- Chemistry and minerals -- Biominerals and their functions in different organisms -- Different types of molecular control in biomineralization -- Enamel: the hardest known biomineral -- Formation of mollusk shells -- The glass house of diatoms -- In vitro studies of mineral-protein interactions -- What can we learn from biology for materials science?- Biomineralization for future research -- Outlook.
Keywords: Biomedical engineering; Biomaterials; Biomedical Engineering and Bioengineering; Biomaterials